NRF2-directed PRPS1 upregulation to promote the progression and metastasis of melanoma - Xiong, Guohang; Feng, Yu; Yi, Xiaojia; Zhang, Xuedan; Li, Xiaoyu; Yang, Lijuan; Yi, Zihan; Sai, Buqing; Yang, Zhe; Zhang, Qiao; Kuang, Yingmin; Zhu, Yuechun (Frontiers in Immunology, 2022)
Phosphoribosyl pyrophosphate synthetase 1 (PRPS1) is the first enzyme in the de novo purine nucleotide synthesis pathway and is essential for cell development. However, the effect of PRPS1 on melanoma proliferation and metastasis remains unclear. This study aimed to investigate the regulatory mechanism of PRPS1 in the malignant progression of melanoma. Here, we found PRPS1 was upregulated in melanoma and melanoma cells. In addition, our data indicated that PRPS1 could promote the proliferation and migration and invasion of melanoma both in vitro and in vivo. PRPS1 also could inhibit melanoma cell apoptosis. Furthermore, we found NRF2 is an upstream transcription factor of PRPS1 that drive malignant progression of melanoma.